Understanding the use of Flexible Work Arrangements Among Older New Zealand Caregivers - Koreshi SY; Alpass F (SAGE Publications, 2023)
Flexibility in the workplace has been suggested to promote prolonged employment among older workers. This study focuses on the question of whether the use of flexible work arrangements (FWAs) differs between caregivers and non-caregivers and how potential differences can be explained. Participants were 296 carers and 1611 non-carers (aged 55–70 years) who completed the 2018 Health, Work and Retirement survey and were in paid employment. Hierarchical regression was used to investigate caregiving as an independent predictor of use of FWAs after controlling for demographic and work-related variables. Results show that caregivers on average used more FWAs than non-caregivers, including flexible work hours, flexible schedules and time off. Differences in FWAs use between caregivers and non-caregivers cannot be explained by differences in socio demographic and work characteristics. The use of FWAs warrants attention in discussions about prolonged employment and reconciliation of care and work among older adults.
Keywords: caregiving; employment; flexible work arrangements; older workers; Humans; Aged; New Zealand; Employment; Retirement; Workplace; Surveys and Questionnaires